PUPUK Bayfolan DAN PUPUK KANDANG SAPI BERPENGARUH KEPADA PERTUMBUHANDAN PRODUKSI KACANG PANJANG (Vigna Sinensis L.) - Dartius ,; Alridiwirsah ,; Eko Saputra Sinaga (AGRIUM: Jurnal Ilmu Pertanian, 2011)
AbstractThis study aims to determine the growth and production of long beans (Vigna sinensis L) on the provision of bayfolan fertilizer and manure cow. The design used was Randomized Design Group factorial with two factors were studied, namely: Fertilizer Bayfolan factor which is denoted by the letter "B" and the stage is divided into 4 cc Bo = 0 (no provision), B1 = 2 cc / liter water, B2 = 4 cc / liter of water, and B3 = 6 cc / liter of water., and Cow manure factors are denoted by the letter "S" is divided into 4 standard, namely S0 = no treatment (control), S1 = 8 kg / plot, S2 = 16 kg / plot, and S3 = 24 kg / plot. Bayfolan fertilizer as the first factor and cow manure as a second factor, while the parameters measured were plant height (cm), number of branches (branches), the age of flowering (days), number of pods per plant (pods), pod length (cm) , and weight of pods (g). Interaction of treatment bayfolan fertilizer and cow manure showed significant differences in plant height parameter, namely the highest plant found in the combination treatment B1S2 (179.67 cm) and lowest in the combination of B0S0 (162.67 cm), the parameter that is the age old flowering flowering the fastest are in the B3S3 combination treatment (21.33 days) and age in combination B0S0 longest flowering (25.00 days). Then the parameters of pod length, pod longest B1S1 contained in the combination treatment (59.12 cm) and shortest on the combination of B0S0 (38.26 cm). And for the heaviest weight of pods found in the combination treatment B1S2 (46.65 g) and lowest in the combination of B0S0 and B0S2 (39.12 g)Keywords: fertilizer, bayfolan, manure cow, production growth, Vigna Sinencis L.